If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5x + 67 = 180 Reorder the terms: 67 + 5x = 180 Solving 67 + 5x = 180 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-67' to each side of the equation. 67 + -67 + 5x = 180 + -67 Combine like terms: 67 + -67 = 0 0 + 5x = 180 + -67 5x = 180 + -67 Combine like terms: 180 + -67 = 113 5x = 113 Divide each side by '5'. x = 22.6 Simplifying x = 22.6
| 25x^2+30x=-9 | | 4(-4x+4)=208 | | -2x^3y+4x^2y^2+70xy^3=0 | | -15-(-2)-(11-6)= | | 4+4x=-7x-40 | | 210=10*w*3 | | 2u+18=7(u+4) | | x-5+x-5+x-5+x-5= | | 136=x^2+16X | | -10-9x=-8x+7 | | -8x+4(x-8)=-36 | | -x*6=-18 | | 3x=4-7x^2 | | 9x+7=180 | | 108+4y=-2y | | (x)+(x+2)=33 | | 6y+3=6-2y | | 5p+d*r=r-7 | | 6x-10=-70-4x | | 5(2x+61x+294)=0 | | 10+3y=0 | | 9x-10x-17=7 | | 8d=-6 | | X-49=12 | | 2x^5+250x^2=0 | | -x+9=-27 | | 5(n+6)+24=-9 | | 54h^2-24k^2=0 | | 3m^2=4m-1 | | x^2-8x+93x-2= | | (-5+i)(-5-i)= | | x=1.2+0.6y |